Analysis of the Potential of the Bumbung Gebyog Dance as an Effort to Develop Cultural Tourism Attractions in the Pinge Tourism Village - I Gusti Made Riko Hendrajana; Parwati, Komang Shanty Muni; Amir, Firlie Lanovia; Putra, I Made Gede Brihanala (Yayasan Sembilan Pemuda Indonesia, 2024)
The development of tourism activities at this time is going well. This can be seen from the development of various tourist attractions starting from the development of tourist villages and special interest attractions to accommodate the needs of tourists. One of the tourist activities that is quite interesting for tourists at this time is cultural tourism. Cultural tourism is said to be able to attract tourists' interest in visiting because when implemented, this tourist activity can invite tourists to learn more about the conditions of community activities, artistic activities and many other things. This research the aim will be to analyze the potential of the Bumbung Gebyog dance and gamelan as a cultural tourism attraction in Pinge Village. The method used in this research is descriptive analysis and observational studies which are more oriented towards the use of qualitative methods in it. Descriptive analysis is used to describe the potential of the Bumbung Gebyog Dance and Gamelan as cultural potential by reading several related research literature and observational studies will be used to ensure the validity of the data that has been obtained through the literature. The results of this research found that Pinge Tourism Village can optimize the potential of the Gebyog Bumbung Dance as the main attraction in developing cultural tourism performances, while ensuring the preservation and preservation of this valuable cultural heritage.